PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA GURU (STUDI PADA SMK BINA PATRIA2 SUKOHARJO) - Saputri, Fortunela Suryo; Nugraheni, Rini (Diponegoro Journal of Management, 2017)
This research  motivated by the decreasing performace level of teachers at  Vocational High School Bina Patria 2 Sukoharjo by showed a decreasing. Because the result of pre-survey showed decrease teachers performance by the compensation and leadership issues. The purpose of this research is to determine the influence of compensation and  and  leadership through to performance of Vocational Hight School Bina Patria 2 Sukoharjo  teachers. Data was collected by using questionnares to 51 employees with sensus sampling method. The techniques of data analysis in this research includes the test of validity, reliability, classical assumptions and multiple regression.The results showing that compensation have positive and significant effect on teachers performance, leadership have positive and significant effect on teachers performance. Based the result, then the recommendation for the school to increase and pay attention on compensating and leadership applied there.